(untitled) (Global Journal of Management and Business Research, 2023)
With its emphasis on innovation and creativity, entrepreneurship education has become a game-changer in the classrooms of the United Kingdom. This article provides a critical analysis of the rising prominence of entrepreneurship education, its effects on the economy and society in the United Kingdom, and its potential to usher in a new era of innovation. The article emphasises university entrepreneurship centres and incubators as hubs for student companies and ventures, highlighting the significance of educational institutions as catalysts for entrepreneurial growth. It also delves into the ways in which teaching young people entrepreneurial skills might help reduce youth unemployment. The need of incorporating entrepreneurship across multiple academic areas is also discussed, as is the influence of social entrepreneurship on local communities. The important conversation also addresses potential hazards, misconceptions, and obstacles to the mainstream adoption of entrepreneurship education, and provides solutions for policymakers and educational stakeholders.